Intermediary Metabolism in Protists: a Sequence-based View of Facultative Anaerobic Metabolism in Evolutionarily Diverse Eukaryotes - Ginger, Michael L.; Fritz-Laylin, Lillian K.; Fulton, Chandler; Cande, W. Zacheus; Dawson, Scott C. (Protist, 2010)
Protists account for the bulk of eukaryotic diversity. Through studies of gene and especially genome sequences the molecular basis for this diversity can be determined. Evident from genome sequencing are examples of versatile metabolism that go far beyond the canonical pathways described for eukaryotes in textbooks. In the last 2-3 years, genome sequencing and transcript profiling has unveiled several examples of heterotrophic and phototrophic protists that are unexpectedly well-equipped for ATP production using a facultative anaerobic metabolism, including some protists that can (Chlamydomonas reinhardtii) or are predicted (Naegleria gruberi, Acanthamoeba castellanii, Amoebidium parasiticum) to produce H2 in their metabolism. It is possible that some enzymes of anaerobic metabolism were acquired and distributed among eukaryotes by lateral transfer, but it is also likely that the common ancestor of eukaryotes already had far more metabolic versatility than was widely thought a few years ago. The discussion of core energy metabolism in unicellular eukaryotes is the subject of this review. Since genomic sequencing has so far only touched the surface of protist diversity, it is anticipated that sequences of additional protists may reveal an even wider range of metabolic capabilities, while simultaneously enriching our understanding of the early evolution of eukaryotes.